Characterization of didactic planning regarding interdisciplinarity in the initial training of teachers of Natural and Mathematical Sciences - Keiciane Canabarro Drehmer-Marques; Inés Prieto Schmidt Sauerwein (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
This study discusses the challenges faced by teachers in initial training in the area of Natural Sciences and Mathematics, in the task of developing interdisciplinary planning. The methodology used was a document analysis of the didactic plans. The objective was to identify the levels of interdisciplinarity achieved in the didactic plans developed by the groups. To classify the plans of the six participating groups, three levels of classification were used regarding interdisciplinarity: level 1, juxtaposition, level 2, integration and level 3, overcoming barriers. The analysis of the results indicates that of the six groups, one group is closer to level 1, three are at level 2, and two groups are close to level 3. The study reinforces the need for greater inclusion of interdisciplinary approaches in initial training courses, so that future teachers can implement them in their professional performance, expanding their didactic-pedagogical repertoire in Basic Education.